(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Given a graph G(V,E) or simply written as G. The graph labeling was first introduced in 1960, it is a function that mapping integers or labels to graph elements (vertices, edges, or both of them) which must satisfy some certain criteria. This concepts was applied in some real problems. In 2007, there was a new concept on labeling, i.e., ``vertex irregular total labeling" and ``edge irregular total labeling". In 2017, there was a new concept, i.e., ``vertex irregular reflexive labeling" and ``edge irregular reflexive labeling". The ``edge irregular reflexive k- labeling" of G is a mapping that puts an even number label from 0 to 2k_v to every vertex and a positive integer label from 1 to k_e to every edge with different weights for each edge. The minimum k of the biggest label among all possible ``edge irregular reflexive k- labeling" of G is called the ``reflexive edge strength" of G, denoted as res(G). There are only few result on ``vertex irregular reflexive labeling" or ``edge irregular reflexive labeling" of corona product graphs. Hence, the purpose of this research are to investigate res of corona product of some ladder graphs and null graphs. Therefore, the goal of this study is to examine the res of corona product of some ladder graphs and null graphs. We get the results as follows: res(SL_n N_m) for ``n 2 and m 1" are ``2nm+3n-33 ceil" for ``2nm+3n-3 ot 2,3 6" and ``2nm+3n-33 ceil+1" for ``2nm+3n-3 2,3 6". Moreover, res(DL_n N_m) for n≥2 and m≥1 are ``2nm+5n-43 ceil" for ``2nm+5n-4 ot 2,3 6" and ``2nm+5n-43 ceil+1" for ``2nm+5n-4 2,3 6". These results contribute to developing the theory of reflexive labeling.